Digital Media in Mathematics Learning to Improve Student Learning Outcomes in Elementary Schools: A Systematic Literature Review - Berta Apriza; Nur Wahyuningsih Ibrahim; Ranti Ayu Kartika (Universitas Pendidikan Ganesha, 2025)
Mathematics learning in elementary schools still faces various obstacles, especially in helping students understand abstract concepts and apply them in real contexts. This study aims to examine the extent to which the use of audiovisual media can improve mathematics learning outcomes in elementary school students. The research subjects were ten scientific articles published within the last five years with special topics on the use of audiovisual media in mathematics learning. The research data were obtained through the Systematic Literature Review (SLR) technique, which includes the stages of identification, screening, and determination of article eligibility based on predetermined inclusion and exclusion criteria. The data collection process was carried out by searching the Google Scholar database. Data analysis used the thematic synthesis method, namely by grouping research findings based on the themes of effectiveness, challenges, and opportunities for audiovisual media development. The results showed that audiovisual media significantly contributed to strengthening concept understanding, increasing learning motivation, and encouraging active student involvement during the mathematics learning process.In addition, it was also found that the successful implementation of audiovisual media is influenced by teacher readiness factors, the availability of technological infrastructure, and the suitability of media with student characteristics. This research contributes a comprehensive picture of the potential as well as the limitations of audiovisual media utilization in basic mathematics education. The findings also have practical implications for teachers, schools and policy makers in designing learning strategies that are more adaptive to technological developments.